Effect of curing method on mechanical and morphological properties of carbon fiber epoxy composites for solid rocket motor. Issue 9 (15th May 2014) - Ma, Renli; Chang, Xinlong; Zhang, Xiaojun; Fang, Pengya; Long, Bing; Liu, Wanlei
<x xml:space="preserve">Abstract</x> Microwave (MW) curing and conventional thermal curing techniques were utilized to cure carbon fiber epoxy composites for solid rocket motor to investigate the effect of curing method on their mechanical and morphological properties. In this work, tensile and inplane shear strength properties together with morphological properties were compared between MW cured and thermally cured composites, and the mechanism for MW curing was analyzed. The study shows that 83% cure cycle time reduction is achieved through MW curing. Mechanism analysis for MW curing indicates the resin at the surface layer and interior parts of the composites is cured with different forms. Temperature monitoring during MW processing indicates the uneven electric field distribution in the domestic MW oven. Fourier transform infrared spectrum measurements reveal that MWs do not initiate any new chemical reactions during the curing process of the composites. Thermal analysis using differential scanning calorimeter reveals higher glass transition temperature (Tg) of MW cured composites compared with thermally cured counterparts. Moreover, the MW cured composites show 17% lower tensile strength than thermally cured composites, whereas a 3% increase of the inplane shear strength is observed for MW cured composites, which is also confirmed via scanning electron microscope by means of better coating the fibers with resin, increased fiber wetting and less fiber pullout. POLYM. COMPOS., 36:1703–1711, 2015. © 2014 Society of Plastics Engineers